Fritzschia furnensis (Marcetia alliance, Melastomataceae): an endangered new species from the State of Minas Gerais, Brazil - Romero, Rosana; Rocha, Maria José Reis Da (Phytotaxa, 2017)
During a floristic survey of Melastomataceae carried out in Delfinópolis and Capitólio, Minas Gerais State, Brazil, a new species of Fritzschia was found. Fritzschia furnensis has stems peeling in thin, woody flakes, petiole 2–10 mm long, large leaf blades (23–38 × 10–29 mm) and an indumentum of glandular trichomes on the branches, petioles, leaves, bracteoles, pedicels, hypanthia, and sepals. The new species is regarded as endangered (EN) due to a restricted distribution, small populations and the destruction of its habitat.